Application of Taguchi Technique and Grey Relational Analysis for Multi-Target Optimization of Two-stage Helical Gearboxes - Hung, Tran Quoc; Tung, Luu Anh (European Journal of Applied Sciences, 2024)
This paper describes an investigation on multi-target optimization of two-stage helical gearboxes with the aim to identify the optimal main design factors to minimize gearbox cross section area and maximize gearbox efficiency. The Taguchi method and grey relation analysis (GRA) were utilized to solve the problem in two processes: first, the single-objective optimization problem was solved to close the gap within variable levels, and then the multi-objective optimization problem was handled to find the optimal main design factors. The coefficients of wheel face width (CWFW) of the first and second stages, the permissible contact stresses (ACS) of the first and second stages, and the first stage’s gear ratio were also selected The outcomes of the research have been utilized to figure out the best values for five major design variables when designing two-stage helical gearboxes.